Metode Pengacakan Algoritma Fisher Yates Pada Game Edukasi Pengenalan Kosakata Bahasa Inggris - Romanus Damanik (Journal Information System Development, 2019)
English is a universal language that is important and has a big role in the world of gaming. Therefore, in order to make children learn English in activities they like. An educational game was made, educational games were built aiming to improve children's ability in terms of English. This game is also designed based on Android so that it makes it easier for players to access games without the need for an internet network to play. In programming, this game implements Fisher Yates algorithm to do the randomization process in the game. The Fisher Yates algorithm is an algorithm for generating a random permutation from a finite set, in other words to randomize a set. This game is played by a player, to complete each level of the game, with the higher level of the game will also increase the level of difficulty. Using a database with SQLite to store player names, questions and levels that have been achieved.